2015
DOI: 10.5423/ppj.nt.06.2015.0107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Systemic Infection and Symptom Expression of Turnip mosaic virus in Chinese cabbage (Brassica campestris)

Abstract: Using the Chinese cabbage (Brassica campestris) cultivar ‘Chun-goang’ as a host and turnip mosaic virus (TuMV) as a pathogen, we studied the effects of ambient temperature (13°C, 18°C, 23°C, 28°C and 33°C) on disease intensity and the speed of systemic infection. The optimal temperature for symptom expression of TuMV was 18–28°C. However, symptoms of viral infection were initiated at 23–28°C and 6 days post infection (dpi). Plants maintained at 33°C were systemically infected as early as 6 dpi and remained sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
2
37
0
3
Order By: Relevance
“…Normally in the field, lilies systemically infected with LMoV and CMV take several weeks to exhibit disease symptoms such as mosaic streaking. This phenomenon was also observed in TMV‐ and TuMV‐infected plants (Yu et al ., ; Chung et al ., ). These might be interpreted as being due to the gradual accumulation of mosaic viral CP in the host chloroplasts (Hodgson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Normally in the field, lilies systemically infected with LMoV and CMV take several weeks to exhibit disease symptoms such as mosaic streaking. This phenomenon was also observed in TMV‐ and TuMV‐infected plants (Yu et al ., ; Chung et al ., ). These might be interpreted as being due to the gradual accumulation of mosaic viral CP in the host chloroplasts (Hodgson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Plant viruses, the major pathogens causing emerging infectious disease (Anderson et al, 2004), exhibit environmental sensitivity of diverse components of their epidemics and thus represent a relatively large threat in the context of global change. For example, recent studies have reported the impacts of high temperatures, water deficit, variable light and CO 2 concentration changes on both rates of infection and transmission efficiencies of viruses (Xu et al, 2008;Nancarrow et al, 2014;Chung et al, 2015;Hily et al, 2016;van Munster et al, 2017;Trebicki et al, 2017;Yvon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous application of stress imposed by heat, drought and TuMV reveals that triple stresses reduce the expression of resistance R genes, increasing susceptibility compared with single stresses (Prasch & Sonnewald, 2015). There is, furthermore, an interaction between high temperature and response to TuMV in Chinese cabbage, with the loss of typical TuMV symptoms at high temperature (Chung et al, 2015). High temperatures are also known to lead to a loss of resistance against Tomato spotted wilt virus (TSWV) (Moury et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Older plants often show a stronger resistance to infection than younger and -tender plants, due to the presence of physical barriers (e.g., hairs, waxes) that prevent insects from probing or feeding on them and delivering the virus. Resistance could also be attributed to volatile emissions that repel insects or stronger antiviral resistances that are active against the delivered viruses (Chung et al, 2015; Fajinmi and Fajinmi, 2010). In addition, in older plants, virus spread into already developed tissues is slower or completely blocked as it follows the source-to-sink route (Roberts et al, 1997), whereas in younger developing plants, systemic spread into new developing tissues occurs quickly.…”
mentioning
confidence: 99%
“…Therefore, other processes in the viral cycle, including replication and spread, must be affected by temperature in this plant-virus interaction (Del Toro et al, 2015; Glasa et al, 2003; Syller, 1987). Whatever the cause, temperature is a major factor affecting the systemic infection of compatible host plants by some positive-sense RNA viruses (Chung et al, 2015; Del Toro et al, 2015). In the case of the PVY-potato system, a model that predicts when, after infection, a potato plant becomes a new source of virus for a vector—or when the plant becomes fully systemically infected by the virus at a certain temperature—would be an important tool to forecast the spread of PVY infection in a crop.…”
mentioning
confidence: 99%